Morphologic HIV demonstration in formalin embedded material–techniques, problems, results - Zietz, Christian; Speiser, B; Hell, W; Stürzl, Michael; Wolf, H; Roth, W K (Verhandlungen der Deutschen Gesellschaft für Pathologie, 1991)
Formalin-fixed, paraffin-embedded material of archival specimens is suitable for a morphological HIV-detection: Infected cells with HIV in the proliferative phase can be demonstrated with reliable results on tissue sections by immunohistological technics using new antibodies. In situ nucleic acid hybridisation technics can also show HIV in the expression phase on paraffin-embedded material, but often fail in demonstrating latently HIV-infected cells. The DNA-Polymerase chain reaction can detect latent Provirus in morphologically defined areas of paraffin sections even in autopsy material, i.e. lymphnodes and even eyes of patients with HIV-Infection, but requires precaution and control with respect to contamination.